THE EMERGING ROLE OF REPETITIVE TRANSCRANIAL MAGNETIC STIMULATION IN TREATING THE MENTAL CONDITION - Amima Salam (Journal of Pakistan Psychiatric Society, 2022)
repetitive Transcranial Magnetic Stimulation (rTMS) is a form of brain stimulation therapy which is approved by FDA (USA) and CE (Europe). In rTMS treatment, an instrument called a stimulator supplies electrical energy to a magnetic coil that generates a magnetic field in the brain for a short period of time. rTMS is based on the principle of electromagnetic induction that can either stimulate or inhibit the neuronal activity of specific brain areas as per need. This drug free treatment is helpful in many neurological and psychological disorders such as depression, OCD, migraines, autism, ADHD, epilepsy, Bipolar and sexual disorders. The treatment is so safe that it could be conducted on one year old child to an old age. It is an outpatient procedure which does not require hospitalization or anesthesia and entails no memory loss. After the session, patients require no recovery period and are able to go about their daily activities immediately following treatment. Other than some precautions, it is often ideal for patients, because it has none of the side effects of traditional medications and other treatments. It can be said rtms is a focal, non-invasive and very well-tolerated form of brain stimulation in clinical use which is safe for almost all patients suffering from mental or psychological disturbance.